2012
DOI: 10.1007/s12263-012-0286-6
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol incorporation in mitochondria and microsomes upon supranutritional vitamin E supplementation

Abstract: Vitamin E (a-tocopherol) is a major lipid-soluble chain-breaking antioxidant in humans and mammals and plays an important role in normal development and physiology. The localization of a-tocopherol within the highly unsaturated phospholipid bilayer of cell membranes provides a means of controlling lipid oxidation at the initiation site. Mitochondria are the site for major oxidative processes and are important in fat oxidation and energy production, but a side effect is leakage of reactive oxygen species. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Such studies showed that increased vitamin E concentration seems to be able to protect livestock muscle from oxidation [45][46][47]. In addition, vitamin E preferentially incorporates into the plasma membrane and the membranes of microsomes and mitochondria [44]. Although the mechanism of vitamin E delivery to cellular organelles has not been defined, its preferential distribution to mitochondria concurs with the observation of the existence of a cytosolic binding protein able to transfer the vitamin from liposomes to mitochondria [40].…”
Section: Vitamin E and Mitochondriamentioning
confidence: 76%
See 1 more Smart Citation
“…Such studies showed that increased vitamin E concentration seems to be able to protect livestock muscle from oxidation [45][46][47]. In addition, vitamin E preferentially incorporates into the plasma membrane and the membranes of microsomes and mitochondria [44]. Although the mechanism of vitamin E delivery to cellular organelles has not been defined, its preferential distribution to mitochondria concurs with the observation of the existence of a cytosolic binding protein able to transfer the vitamin from liposomes to mitochondria [40].…”
Section: Vitamin E and Mitochondriamentioning
confidence: 76%
“…Few data exist on the effect of in vivo vitamin E supplementation in mitochondria. Some information is available on the changes in mitochondrial vitamin E levels from studies on skeletal muscle of livestock, performed to improve food muscle resistance to lipid oxidation [44]. Such studies showed that increased vitamin E concentration seems to be able to protect livestock muscle from oxidation [45][46][47].…”
Section: Vitamin E and Mitochondriamentioning
confidence: 99%
“…A study by Rajasekaran et al proposed that the regulation of a-tocopherol levels in membranes is critically important to maintain the erythrocyte membrane structure and function (42). Recently, it has been hypothesized that a-tocopherol partitions into domains of membranes that are rich in polyunsaturated phospholipids, amplifying the concentration of the vitamin where it is most needed (43). The presented results indicated that vitamin E in erythrocytes did not change after LDL-apheresis and showed only a slight increase (although it was significant) after rheohaemapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…The main antioxidant enzymes include thioredoxin 2 (TRX2), thioredoxin reductase (TXNRD2), the glutaredoxins 2 (GLRX2) and 5 (GLRX5), the peroxiredoxins 3 (PRDX3) and 5 (PRDX5), GSH peroxidase 1 (GPX1), oxidized glutathione (GSSG) reductase (GSR), and the copper/zinc (SOD1)-and manganese (SOD2)-containing SODs (Kalinina et al, 2008). The major non-enzymatic antioxidants are GSH, coenzyme A (CoA-SH; for more details, see The Redox Metabolism of PeroxisomesAntioxidant Systems), ubiquinol (Maroz et al, 2009), vitamin C, andvitamin E (Sagun et al, 2005;Marí et al, 2009;Lauridsen and Jensen, 2012). Vitamin E, a fat-soluble nutrient, is present in relatively low concentrations in mitochondria, and its main function is to trap LOO • , thereby preventing the propagation of lipid peroxidation (Forkink et al, 2010).…”
Section: Antioxidant Systemsmentioning
confidence: 99%